基于ANSYS/LS-DYNA的齿轮传动冲击特性仿真分析 - 张发民 (Jixie chuandong)
The simulation model of gear transmission impact characteristic is established by using the ANSYS/LS-DYNA software based on the continuous medium ware theory.The curves of the meshing force and dynamic load between gear tooth surface changing with time,and the dynamic response curve of driven gear rotational speed curve under different load and initial conditions are acquired.The reliable basis for gear strength analysis is provided.